2009
DOI: 10.1016/j.atmosenv.2008.09.085
|View full text |Cite
|
Sign up to set email alerts
|

Trends in on-road vehicle emissions of ammonia

Abstract: rates from diesel trucks were difficult to measure in the tunnel setting due to the large contribution to ammonia concentrations in a mixed-traffic bore that were assigned to light-duty vehicle emissions. Nevertheless, it is clear that heavy-duty diesel trucks are a minor source of ammonia emissions compared to light-duty gasoline vehicles.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 24 publications
5
80
0
3
Order By: Relevance
“…In some regions both sources are important, particularly in regions of mixed land use, such as Denver and Los Angeles (Sun et al, 2017). The eastern portions of the Los Angeles Air Basin are strongly influenced by mobile sources Kean et al, 2009, Leifer et al, 2017. Fraser and Cass (1998) reported that NH 3 emissions from light-duty motor vehicles equipped with three-way catalytic converters are similar in magnitude to agricultural emissions in the Los Angeles Air Basin.…”
Section: Magnitude Of Agricultural and On-road Emissions Of Nhmentioning
confidence: 98%
See 1 more Smart Citation
“…In some regions both sources are important, particularly in regions of mixed land use, such as Denver and Los Angeles (Sun et al, 2017). The eastern portions of the Los Angeles Air Basin are strongly influenced by mobile sources Kean et al, 2009, Leifer et al, 2017. Fraser and Cass (1998) reported that NH 3 emissions from light-duty motor vehicles equipped with three-way catalytic converters are similar in magnitude to agricultural emissions in the Los Angeles Air Basin.…”
Section: Magnitude Of Agricultural and On-road Emissions Of Nhmentioning
confidence: 98%
“…Estimated emissions of NH 3 in the United States increased by 91, 70 and 7% in the on-road, power plant and agricultural sectors, respectively, between 1990 and 2010 (Xing et al, 2013). Emissions of NH 3 from motor vehicles (Kean et al, 2009;Leip et al, 2011) and industrial stacks (Hertel et al, 2011;Li et al, 2017;Vallero, 2014) are largely a byproduct of stringent NO x control technologies. In many regions of the developed world, NO x emissions have steadily declined since around 1990 (Leip et al, 2011) while emissions of NH 3 have remained constant or increased slightly, such as in the United States where NH 3 emissions have increased by 11% (Bytnerowicz et al, 2016;Hertel et al, 2011;Xing et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Annual emissions of NO x and NH 3 in the contiguous US in 2010 are shown in Table 2. Mobile emissions of NH 3 are not shown explicitly here, as they are < 4 % of the US total in the NEI2008, although this may be an underestimate in urban areas (Kean et al, 2009). Anthropogenic sources of NO x includes surface sources, electric generating units (EGUs), and non-EGU industrial point sources.…”
Section: Geos-chem Model Descriptionmentioning
confidence: 99%
“…And the non-agricultural sources include -wild animals (Anderson et al, 2003;Riddick et al, 2012;Simpson et al, 1999;Sutton et al, 2000a;Theobald et al, 2006); -catalyst processes, mainly related to road traffic (Kean et al, 2009;van Vuuren et al, 2011); , and the right side of the figure illustrates the pathway of nitrogen oxides (NO y ) compounds in the atmosphere (NO x = NO + NO 2 and reaction products). The sketch is a modified version of the figure in Hertel et al (2006).…”
Section: Ammonia Emissionsmentioning
confidence: 99%